A Survey of Heart Rot in Some Plantations of Acacia mangium Willd. In Sabah. - Mahmud Sudin; Susee Lee (1993)
Only 4% of thinnings had heart rot which appeared to originate from thinning wounds. In the older trees, the average incidence of heart rot was 35.5%. -from Authors